Simulation
VI, 211 p.
Keywords: This book examines the historical roots and evolution of simulation from an epistemological, institutional and technical perspective. Rich case studies go far beyond documentation of simulation’s capacity for application in many domains, they also explore the "functional" and "structural" debate that continues to traverse simulation thought and action. One here asks if simulation deeply transforms science, or instead constitutes a limited tool that principally extends the repertory of erstwhile practice. Does simulation comprise a novel form of experiment, or rather operate as a mechanism which extends standing forms of experimentation? What are simulation’s relations with models or theory, for example? These studies further query to what extent and in what ways simulation may be regarded as a discipline, a special species of instrument, or as transdisciplinary.